IMPLEMENTATION OF INDUSTRIAL RELATIONS POLICY AT PT. YULIANI AMANAH CONSTRUCTION IN PETASIA TIMUR DISTRICT, NORTH MOROWALI REGENCY - Yuliani; Irfan Mufti; Dandan Haryono (RADJA PUBLIKA, 2025)
This study aims to analyze the implementation of industrial relations policies at PT. Yuliani Amanah Construction in Petasia Timur District, North Morowali Regency, using Grindle's (1980) policy implementation theory approach, which emphasizes two main dimensions: content of policy and context of implementation. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with key informants consisting of company management, employees, and representatives from the North Morowali Manpower and Transmigration Office. The research results show that in terms of the content of policy, industrial relations policy implementation has not been optimal due to limited resources, poor understanding among policy implementers at the company level, and weak fulfillment of workers' rights, such as minimum wages, occupational safety (K3) standards, and labor dispute resolution mechanisms. Meanwhile, in terms of the context of implementation, power factors, economic interests, and regional socio-economic stability significantly influence policy implementation. Local governments place greater emphasis on investment stability than on firm enforcement of labor laws. These findings reinforce Grindle's (1980) view that the effectiveness of policy implementation in developing countries depends heavily on the interaction between the policy's substance and the sociopolitical context in which it is implemented. This study recommends strengthening the institutional capacity of labor inspectors, increasing company management awareness of regulatory compliance, and establishing a tripartite dialogue forum between the government, companies, and workers to create harmonious and equitable industrial relations.